Prospective study of post-operative hyponatremia in patients undergoing lower-limb orthopedic surgery - Nirmaladevi S; Gokul R; Arulanandam R; Ilamparithi Jayaraman (Asian Journal of Medical Sciences, 2024)
Background: Hyponatremia is a common electrolyte imbalance in hospitalized patients, including those undergoing orthopedic surgery. It is associated with increased mortality and morbidity. Early symptoms of hyponatremia are often vague and can be mistaken for normal post-operative sequelae. Therefore, it is important to be aware of hyponatremia’s risk factors and symptoms in post-operative orthopedic patients, especially in older patients. Aims and Objectives: The aims and objectives are to study the incidence of post-operative hyponatremia in patients undergoing lower-limb orthopedic surgery. Materials and Methods: This prospective observational study was done on 140 elective and emergency lower-limb surgery patients. The patients were divided into two groups based on their age. Group A comprised 70 patients under 65, and Group B comprised 70 patients over 65. The patients underwent pre-operative assessments, including complete physical and systemic examinations and routine pre-operative workups, including checking serum sodium and potassium levels. Results: In a study of 140 post-operative orthopedic patients, 55 (39%) had low serum sodium levels on post-operative day 1. Of these, 46 had mild hyponatremia, 7 had moderate hyponatremia, and 2 had severe hyponatremia. Elderly patients were more likely to develop hyponatremia than younger patients (27% vs. 12%, P=0.003). The most common symptoms of hyponatremia were headache (8.6%), nausea (3.6%), lethargy (7.1%), confusion (6.4%), and disorientation (1.4%). Hyponatremic patients had longer hospital stays than normal patients (13 days vs. 5–11 days). Conclusion: The elderly population had a higher incidence of post-operative hyponatremia and was more vulnerable to developing symptoms. Although hyponatremia following surgery is common after orthopedic surgeries, it is primary, temporary, and easily treatable.